Assessing The Effectiveness Of Concept Mapping As Problem-Based Learning In Teaching-Learning Processes - SONG CHUNYAN; NIDHI AGARWAL; AMINUL ISLAM (Revista Electronica de Veterinaria, 2024)
Individuals who are successful in medicine possess knowledge structures that are composed of extensive, integrated frameworks of interconnected subjects. This is true whether they are students or working-level physicians. The development of this knowledge base has the potential to provide a wide range of outcomes, one of which is the enhancement of clinical problem-solving abilities, in addition to other higher-level cognitive processes. It is possible to examine how pupils conceptualise the concepts that provide the foundation of the knowledge that they have been taught via the use of a method known as concept mapping. Students may use concept maps as a support tool while they are working on problem-based learning (PBL) assignments. Concept maps are based on ideas that are derived from the academic area of learning theory. Within the context of problem-based learning (PBL) classrooms, students can create concept maps that include key scientific and social ideas within the context of PBL situations. There are several potential benefits associated with the use of concept maps in project-based learning (PBL) sessions. These benefits include the promotion of communication, the identification of knowledge gaps, the generation of ideas for learning objectives, the stimulation of application across disciplinary boundaries, and the evaluation of each student’s progress. Students may also find concept mapping to be effective in other types of project-based learning (PBL) settings, such as large-scale seminar discussions and settings that emphasise team-based learning. Using these types of Problem-Based Learning (PBL) situations, students have the potential to acquire a more profound comprehension of the connections that exist between various ideas and the PBL case that is being investigated. The development of instruments that are dependable and supported by evidence of validity is one of the obstacles that prevent concept mapping from being extensively used in the field of medical education.